The Pro-Apoptotic Effect of Diallyl Trisulfide (DATS) on MDA-MB-231 Breast Cancer Cells - Ailany, Erla Syah Dilla; Veterini, Lysa; Putri, Winawati Eka; Kurniasari, Diyan Wahyu (UNUSA Press, 2025)
Introduction: Breast cancer is the most prevalent cancer globally, impacting almost 2.1 million people each year. The MDA-MB-231 exemplifies the aggressive nature of the triple-negative breast cancer (TNBC) subtype. Diallyl Trisulfide (DATS) in Allium sativum (garlic) demonstrates potential anticancer characteristics primarily by causing the generation of ROS that may trigger apoptosis. Objective: The study evaluates the effect of DATS on apoptosis in MDA-MB-231 cells via the ROS pathway. Methods: An in vitro study utilizing MDA-MB-231 cells, categorized into four groups: (1) Medium control, (2) Negative control, (3) 20 µM DATS after 24 hours, and (4) 40 µM DATS after 24 hours. The study used Annexin V-FITC/PI flow cytometry to measure apoptotic cell death, the MTT assay to measure cell viability, and DCFH-DA fluorescence to measure ROS production. Results: Cell viability was decreased after DATS treatment and a substantial increase in intracellular ROS production was observed that varies with time and dose (p < 0.001). In comparison to the other groups, the group that received 40 µM DATS for 24 hours had the highest rate of apoptosis and the largest accumulation of reactive oxygen species (ROS). Conclusions: DATS significantly elevates intracellular ROS levels to promote apoptosis in MDA-MB-231 cells as a pro-oxidant therapy for aggressive breast cancer.